Thermo-mechanical analysis of non-pneumatic rubber tyres. - Harwood, Stephen (Curtin University, 1999)
This thesis is concerned with the design, analysis and optimisation of semi-solid or non- pneumatic tyres. More specifically, the thesis is intended to show how the FEA software package Abaqus can be used to determine whether or not an AirBoss tyre meets performance criteria in regards load/deformation criteria and if there is a likelihood of failure through overheating of the tyre during service.The work is intended to clearly explain the nature of natural rubber from a molecular description through to phenomenological descriptions used to solve for stresses, strains, creep and relaxation phenomena and temperature generation through hysteresis losses within the structure of the rubber compound.The thesis examines practical ways to obtain data for use in the analysis and describes test equipment (both "off-the-shelf" and purpose built) to obtain the required information.The objective is to progress, step by step, through the stages of analysis beginning with information to predict static loading conditions for the tyre. Viscoelastic behaviour, such as creep and relaxation are predicted and then tested to determine the correlation and refine test data before proceeding to the next stage of analysis.Ultimately, a prediction is made as to the temperature distribution throughout a section of the non-pneumatic tyre. A testing rig is described which has been built to test the analysis and enable a comparison to be made between FEA prediction and "real life".